OPTIMALISASI FUNGSI INTERMEDIASI PERBANKAN SYARIAH BERBASIS SEKTORAL DI ERA OTONOMI DAERAH - Nugroho, Muh Rudi (Jurnal Ekonomi & Studi Pembangunan, 2016)
This study aims to analyze by simulating the growth of Islamic banking if synergy with state agencies/areas of financial management. In this simulation, third-party funds proxied by 10% of the provincial budget funds (APBD). Using regression analysis, 10% of funds allocated APDB implications for the development of the province of Islamic banking, which is measured by the amount of credit distribution. This condition indicates that optimization of the Islamic banking intermediation function can be conducted based sector in the era of regional autonomy, because it has mulplier effect, both on Islamic banking and government. By sector, the nine sector contributed to provincial GDP will increase along with the increase in Islamic banking credit distribution. On the other hand, the increase in deposits will have a positive impact on GDP rising in some sectors. To support the optimization process of Islamic banking intermediation, the Islamic banking should be directed to investment banks, so that Islamic banking and regional development in the era of regional autonomy can be run together. This research is expected to contribute to the financial management of the country/region that has implications for the development of Islamic banking, through the regulation of the Ministry of Finance and Bank Indonesia.